The effect of 3D transport-induced disequilibrium carbon chemistry on the atmospheric structure, phase curves, and emission spectra of hot Jupiter HD 189733b - Steinrueck, ME; Parmentier, V; Showman, AP; Lothringer, JD; Lupu, RE (IOP Publishing, 2019)
On hot Jupiter exoplanets, strong horizontal and vertical winds should homogenize the abundances of the important absorbers CH4 and CO much faster than chemical reactions restore chemical equilibrium. This effect, typically neglected in general circulation models (GCMs), has been suggested to explain discrepancies between observed infrared light curves and those predicted by GCMs. On the nightsides of several hot Jupiters, GCMs predict outgoing fluxes that are too large, especially in the Spitzer 4.5 μm band. We modified the SPARC/MITgcm to include disequilibrium abundances of CH4, CO, and H2O by assuming that the CH4/CO ratio is constant throughout the simulation domain. We ran simulations of hot Jupiter HD 189733b with eight CH4/CO ratios. In the more likely CO-dominated regime, we find temperature changes ≥50–100 K compared to the simulation for equilibrium chemistry across large regions. This effect is large enough to affect predicted emission spectra and should thus be included in GCMs of hot Jupiters with equilibrium temperatures between 600 and 1300 K. We find that spectra in regions with strong methane absorption, including the Spitzer 3.6 and 8 μm bands, are strongly impacted by disequilibrium abundances. We expect chemical quenching to result in much larger nightside fluxes in the 3.6 μm band, in stark contrast to observations. Meanwhile, we find almost no effect on predicted observations in the 4.5 μm band, because the changes in opacity due to CO and H2O offset each other. We thus conclude that disequilibrium carbon chemistry cannot explain the observed low nightside fluxes in the 4.5 μm band.